2016
DOI: 10.1128/aac.02445-15
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Polymyxin B Biodistribution and Disposition in an Animal Model

Abstract: Despite dose-limiting nephrotoxicity concerns, polymyxin B has resurged as the treatment of last resort for multidrug-resistant Gram-negative bacterial infections. However, the pharmacokinetic, pharmacodynamic, and nephrotoxic properties of polymyxin B still are not thoroughly understood. The objective of this study was to provide additional insights into the overall biodistribution and disposition of polymyxin B in an animal model. Sprague-Dawley rats were dosed with intravenous polymyxin B (3 mg/kg of body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 25 publications
3
45
0
Order By: Relevance
“…For PMB, after even a single intravenous dose, the mean kidney homogenate-to-serum concentration ratios were 7.45 and 19.6 at 3 h and 6 h postdose, respectively (28). The ratios for kidney were substantially higher than those for heart, lung, liver, spleen, and muscle.…”
Section: To What Extent Do Polymyxins Accumulate In the Kidney And Whmentioning
confidence: 93%
See 2 more Smart Citations
“…For PMB, after even a single intravenous dose, the mean kidney homogenate-to-serum concentration ratios were 7.45 and 19.6 at 3 h and 6 h postdose, respectively (28). The ratios for kidney were substantially higher than those for heart, lung, liver, spleen, and muscle.…”
Section: To What Extent Do Polymyxins Accumulate In the Kidney And Whmentioning
confidence: 93%
“…The ratios for kidney were substantially higher than those for heart, lung, liver, spleen, and muscle. Because the ratios in these studies were for kidney homogenate (27,28), they would underestimate the concentration in the region of the greatest polymyxin accumulation. Immunostaining studies of sections of rodent kidneys from animals treated with PMB have shown that accumulation occurs predominantly in the renal cortex, primarily within proximal tubular cells (28,29).…”
Section: To What Extent Do Polymyxins Accumulate In the Kidney And Whmentioning
confidence: 99%
See 1 more Smart Citation
“…Colistin is a polycation with 5 free amino groups that may, in part, be responsible for its ability to bind electrostatically to negatively charged tissue phospholipids (42,43). Animal studies have shown that colistin and polymyxin B accumulate in tissues, including the lungs (44)(45)(46). Unlike colistin, CMS has poor tissue binding properties which may be attributed to the amine side chains protected by sulfomethyl groups (2,43,45).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence suggesting that polymyxin B is not eliminated through the renal route (5,6). However, pharmacokinetic studies have reported preferential accumulation and prolonged residence of polymyxin B in rat kidneys (7,8). Several studies have also reported a daily dose of polymyxin B as an independent risk factor associated with drug nephrotoxicity (9)(10)(11).…”
mentioning
confidence: 99%